The role of orexin and MCH neurons in the hypothalamus in sleep-wake regulation and learning-forgetting balance - Li, Penghong; Zhu, Jing; Zhang, Huijuan; Ma, Guorui; Li, Xintong; Ding, Yuxin; Hou, Xuefei; Li, Xin (Frontiers in Neuroscience, 2025)
Orexin (Orx) and melanin-concentrating hormone (MCH) neurons in the lateral hypothalamic area are central to regulating the sleep-wake cycle and coordinating memory consolidation and forgetting through dynamic homeostatic mechanisms. This review systematically examines the functional characteristics of these two neural systems and their interactions: first, MCH neurons facilitate the transition from non-rapid eye movement (NREM) to rapid eye movement (REM) sleep at night via a dual regulatory mechanism and regulate the active forgetting of memories via hippocampal neural circuits; second, orexin neurons maintain homeostasis in daytime wakefulness via monoaminergic and cholinergic pathways, while acting as stabilizers during REM sleep stages and enhance memory encoding through amygdala-prefrontal projections. Notably, these two systems show unique antagonistic synergetic dual-mode regulation under the framework of circadian rhythm: orexin neurons maintain the steady state of sleep-wake cycle by promoting wakefulness and inhibiting REM sleep and MCH neurons form dynamic antagonism by inducing sleep and enhancing REM sleep in the sleep-wake dimension, whereas a coordinated balance of information filtering is achieved in the memory regulation dimension through phasic encoding of hippocampal theta rhythms. Clinically, orexin receptor agonists demonstrate therapeutic potential in narcolepsy management, whereas MCH receptor antagonists show promise for memory reconsolidation in post-traumatic stress disorder (PTSD). This review emphasizes the dynamic interplay and reciprocal inhibition between orexin and MCH neurons that form a pivotal bidirectional network framework for dissecting neuropsychiatric comorbidities, wherein pathway dysregulation may propagate from circadian disruption to mnemonic dysfunction, which provides a new theoretical framework for developing intervention strategies across symptom dimensions.